2004
DOI: 10.1111/j.1600-0714.2004.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Nimesulide and indomethacin induce apoptosis in head and neck cancer cells

Abstract: The results of our study on HNSCC cells together with data from different studies showing anti-cancer activity of NSAIDs suggest that COX inhibitors could play a role in HNSCC treatment and prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Liu et al found a radiosensitizing effect of the selective COX-2 inhibitor celecoxib in breast tumor cell line MCa-35 but not in lung carcinoma cell line A549, although both cell lines express COX-2 [25]. Both cell lines used for our study, SCC25 and SCC9, express COX-2 as has recently been demonstrated by our group [33], but neither of them is radiosensitized by the COX-2 inhibitor nimesulide. Taken together, these observations may indicate that some effects of selective COX-2 inhibitors are cell-type-or tissue-type-specific.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Liu et al found a radiosensitizing effect of the selective COX-2 inhibitor celecoxib in breast tumor cell line MCa-35 but not in lung carcinoma cell line A549, although both cell lines express COX-2 [25]. Both cell lines used for our study, SCC25 and SCC9, express COX-2 as has recently been demonstrated by our group [33], but neither of them is radiosensitized by the COX-2 inhibitor nimesulide. Taken together, these observations may indicate that some effects of selective COX-2 inhibitors are cell-type-or tissue-type-specific.…”
Section: Discussionsupporting
confidence: 47%
“…Our group has recently reported high-level expression of COX-2 enzyme in these cells [33]. At first, we determined the effect of irradiation on cell survival in both cell lines.…”
Section: Effect Of Irradiation Alone or In Combination With Nimesulidmentioning
confidence: 99%
“…30 As we demonstrated recently in our laboratory, nimesulide induced apoptosis in head and neck cancer cell lines. 17 In this study, we demonstrated that the selective COX-2 inhibitor nimesulide is also antiproliferative against HNSCC cell lines, possibly because of the reduction of the protooncogenes Ets-1 and Ets-2.…”
Section: Discussionmentioning
confidence: 95%
“…7 Recently, we showed in our laboratory that nimesulide was able to induce apoptosis in head and neck cancer cell lines SCC-9 and SCC-25. 17 In this study, we investigated the effect of nimesulide on the expression of two transcription factors, protooncogenes Ets-1 and Ets-2, in HNSCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, nimesulide is a highly selective COX-2 inhibitor and its cytotoxic effects have been evaluated in some cancer cell lines such as head and neck squamous cell carcinoma, colon carcinoma and pancreatic cancer (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%